Waterfowl potential as resevoirs of high pathogenic avian influenza H5N1 viruses - R Susanti; R.D Soejoedono; I-G.N.K Mahardika; I-W.T Wibawan; M.T Suhartono (Indonesian Center for Animal Research and Development (ICARD), 2007)
The high population of waterfowl subsequently with the high case fatality of poultry and people in West Java regency caused by HPAI H5N1 can raise possibility that waterfowl was a natural reservoir. This research aimed to prove that waterfowl in West Java served as reservoir of AI virus (primarily H5N1) and also identify the virus pathotype based on cleavage site of amino acid sequence. Cloacal swab sample was obtained from healthy and unvaccinated waterfowl from Sukabumi and Bogor Regency. Cloacal swab was propagated in 9 days old embryonic chicken eggs. Allantoic fluid was harvested at the 4th day of incubation and then tested for hemagglutination, and positive isolate continued with virus sub-typing using PCR method. H5 gene from H5N1 isolate then sequenced using dideoxy termination method. Multiple alignment of nucleotide sequences were analysed using MEGA-3.1 program. Sub-typing using PCR method indicated the existence of 25 strain H5N1, 16 strain HxN1, 4 strain H5Nx and 9 virus ND. Characterization of cleavage site amino acid sequence indicated that all H5N1 sample were pathogenic with sequence QRERRRKKR (23 sample) dan QRESRRKKR (2 sample). Waterfowl was HPAI H5N1 virus reservoir. Asymptomatic infection in waterfowl, but the virus shedding gradually occurred and therefore it became potential source of H5N1 virus infection. Our findings suggest that immediate action is needed to prevent the transmission of highly pathogenic avian influenza viruses from the apparently healthy waterfowl into terrestrial poultry or human. Key Words: HPAI, H5N1, Reservoir, Water Fowl